The meaning(s) in law and language - Accetto, Matej (Linguistica (Ljubljana), 2013)
This paper revisits the delicate relation between law and language, with language inevitable serving as the vehicle of legal deliberations and pronouncements, and in particular their seemingly irreconcilable qualities: while law is predicated on the concept of the rule of law (or Rechtsstaat) which in turn calls for a clear and predictable system of norms ensuring equal treatment, language is often indeterminate or ambiguous, the meaning of words unclear or uncertain. Is language even properly equipped to perform the role asked of it by law? This question is addressed by outlining and analysing the path traversed from the open-ended vagueness of linguistic terms to the uncompromising confines of their legal interpretation, both in the course of adopting legislation and in particular in the course of adopting judicial pronouncements on the meaning of linguistic terms employed.
Keywords: appréciation judiciaire; droit comparé; droit et langue; interprétation juridique; jezikoslovje; law; linguistics; pravne razlage; pravo; primerjalno pravo; sodna presoja